Anti-Jo-1 myositis and the antiphospholipid syndrome showing right ventricular thrombus: a novel overlap syndrome with atypical presentation. Issue 5 (September 2014) - Wang, Ching-Hsun; Wang, Ning-Chi; Lin, Te-Yu; Chen, Chen-Hung
Abstract It has long been recognized that patients with myositis and positive anti-Jo1 antibody tend to be associated with interstitial lung disease. Recent studies revealed that such patients may also have fever, Raynaud's phenomenon, mechanic's hand, polyarthralgia, or usually mild, self-limiting, non-erosive or erosive polyarthritis known as antisynthetase syndrome. The hallmark of this disorder is the presence of the autoantibodies that recognize the aminoacyl-tRNA synthetases, which play a critical role in protein synthesis. The most well recognized of the autoantibodies is anti-histidyl (Jo-1). Antisynthetase syndrome cases associated with other autoimmune diseases are rarely reported. We here present a case of antisynthetase syndrome presented with right ventricle thrombus and deep vein thrombosis in the lower limbs. Secondary antiphospholipid syndrome was then diagnosed after a series of examinations. The patient was successfully treated with anticoagulant alone without surgical thrombectomy. Our case revealed that clinical physicians should watch for thrombotic complications when facing patients with antisynthetase syndrome. Medical therapy with anticoagulants alone may be an alternative treatment option in patients with right ventricle thrombus who cannot tolerate surgical thrombectomy.